2012
DOI: 10.1371/journal.pone.0036859
|View full text |Cite
|
Sign up to set email alerts
|

Retinotopic Maps, Spatial Tuning, and Locations of Human Visual Areas in Surface Coordinates Characterized with Multifocal and Blocked fMRI Designs

Abstract: The localization of visual areas in the human cortex is typically based on mapping the retinotopic organization with functional magnetic resonance imaging (fMRI). The most common approach is to encode the response phase for a slowly moving visual stimulus and to present the result on an individual's reconstructed cortical surface. The main aims of this study were to develop complementary general linear model (GLM)-based retinotopic mapping methods and to characterize the inter-individual variability of the vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 65 publications
4
45
0
Order By: Relevance
“…This, in turn, would be in agreement with recent evidence that hOcV4 might contain a complete hemi-field representation (Wilms et al, 2010). Based on our results, it could thus be assumed that cytoarchitectonic area hOcV4 could be regarded as the microstructural correlate of the retinotopically defined hemifield hV4 (Henriksson et al, 2012;Winawer et al, 2010).…”
Section: 2supporting
confidence: 92%
See 1 more Smart Citation
“…This, in turn, would be in agreement with recent evidence that hOcV4 might contain a complete hemi-field representation (Wilms et al, 2010). Based on our results, it could thus be assumed that cytoarchitectonic area hOcV4 could be regarded as the microstructural correlate of the retinotopically defined hemifield hV4 (Henriksson et al, 2012;Winawer et al, 2010).…”
Section: 2supporting
confidence: 92%
“…Later, retinotopic mapping studies provided evidence for a complete hemi-field representation within the cortex directly anterior to area V3v (Brewer, Liu, Wade, & Wandell, 2005;Wade, Brewer, Rieger, & Wandell, 2002;Winawer, Horiguchi, Sayres, Amano, & Wandell, 2010). The edges of this hemi-field representation, termed human V4 (hV4) indeed responded to stimuli at the upper and lower vertical meridian (Henriksson, Karvonen, Salminen-Vaparanta, Railo, & Vanni, 2012;Winawer et al, 2010).…”
Section: 2mentioning
confidence: 99%
“…The borders between these areas represent the lower (V3/LO-1) and upper (LO-1/LO-2) vertical meridian. These and the studies of Swisher et al (2007), Wandell et al (2007), Kolster et al (2010) and Henriksson et al (2012) have established LO-1 and LO-2 as distinct, functionally defined areas within the higher lateral extrastriate human visual cortex. Furthermore, recent studies have demonstrated functional differences between LO-1 and LO-2.…”
Section: Introductionmentioning
confidence: 82%
“…The stimulus position was randomized across the display at 61 positions, which consisted of the central fixation location and 5 levels of eccentricity (e.g., visual angles of 0.7°-2.5°, 2.5°-5°, 5°-10°, 10°-15°, and 15°-20°) and 12 polar angles, as depicted in Fig. 1B (right panel), similar to those employed in previous studies (Hansen et al, 2004, Henriksson et al, 2012. A sequence of mapping stimuli appeared up to 7 (for monkey Q) or 4 (for monkey B) times during a single fixation.…”
Section: Retinotopic Mapping Task and Data Acquisitionmentioning
confidence: 99%